The Intersection of Gender, Race and Social Class in Gabriela Garcia's Of Women and Salt - Nihayah Nayyiroh (Fakultas Ilmu Budaya, 2025)
Intersectionality of Gender, Race and Social Class in Gabriela Garcia’s Of Women and Salt: Nihayah Nayyiroh, 190110101008, 2025; 53 pages; English Department, Faculty of Humanities, Universitas Jember. This study discusses the intersectionality of gender, race, and social class in Gabriela Garcia's novel Of Women and Salt. The term “intersectionality” arises when individuals with multiple social identities, such as gender, race, and social class, experience intertwined forms of oppression. In this novel, intersectionality is demonstrated through the experiences of Latin women who face various forms of violence and social injustice. The research method used is descriptive qualitative, employing the sociology of literature approach of Diana T. Laurenson and Alan Swingewood to analyze social phenomena such as oppression, violence, and so on that occur in the novel. Additionally, the concept of intersectionality by Patricia Hill Collins and Bilge is used to reveal the forms of these phenomena that influence the lives of the characters. The results of this research reveal that the intersection of social identities such as gender, race, and social class forms oppression against the main female characters: María Isabel, Dolores, Carmen, Jeanette, Gloria, and Ana. They experience different forms of oppression: María is discriminated against because she is the only female worker in the cigar factory; Dolores experiences domestic violence, and Carmen witnesses violence committed by her father, Hernandez; Jeanette is a survivor of sexual abuse and a drug addict; and Gloria and Ana are immigrants from El Salvador who left their home country to escape civil conflict and violence there.
:: Finalisasi file repositori 16 Juli 2026_Kurnadi
Keywords: Domestic Violence; Intersection; Immigrants.